Life of Jesus: who he is and why he matters - Dickson, John (Zondervan, 2010)
Jesus as a tangible sign of God's interest in our world -- The identity of Jesus and his critique of "religion" -- Jesus : vision of the future and its relevance now -- Jesus : thoughts on "religious hypocrites" and "rotten sinners" -- Jesus : death as the source of life -- How could it happen? what does it matter? -- Discussion guide for the six-session video curriculum